The Effectiveness Of Motor Vehicle Tax Collection On Increasing West Java Regional Original Income - Asri Ayu Lestari; Okkeu Fhenica Wini Sari; Karyadi (Universitas Sains dan Teknologi Komputer, 2021)
The implementation of tax autonomy by the central and regional governments separately provides the flexibility to be more independent in tax arrangements in order to increase the income of each region. The objective of this research is to determine whether the West Java provincial government's application of vehicle tax collection is effective in increasing Regional Original Income (ROI) in West Java. The methodology used in this research is qualitative. Analysis of the data used is analysis by calculating the effectiveness of tax collection. The results of data analysis show that the efficiency of vehicle tax collection has an impact on increasing local revenue in West Java.